KAIDAH FIQHIYYAH DALAM SURAT AL-BAQARAH AYAT: 183, 184, 185 DAN 187 - Aulia, Clarisa; Fatimah, Suciati; Maulana, Ahmad; Taqiyuddin, Hafidz (Sekolah Tinggi Islam Syariah (STIS) Al-Ittihad Bima, 2025)
This article discusses the importance of thoroughly understanding the history, development, and interpretation of the fasting ordinance in Islam, especially analyzing Surah Al-Baqarah verses: 183, 184, 185 and 187 relating to Ramadan fasting. The focus of this study is to identify the fiqhiyyah rules contained in the verse and explain how the fasting law has changed from the beginning of Islam to become an obligation. In its discussion, the article reviews the differences in scholarly views regarding the equality of Muslim fasting with the previous people. Furthermore, this research uses the content analysis method to analyze, identify, and interpret the fiqhiyyah rules contained in Surah Al-Baqarah and relate them to the context in which the verse was revealed (asbabun nuzul). With the content analysis method approach, this article aims to provide an in-depth understanding of the history of the fasting ordinance, the interpretation of the verse, the reason for the verse's revelation, and its relation to the ushul fiqh rules. The results show the existence of provisions and prohibitions in carrying out fasting, differences in scholarly views regarding the application of verses, and the relevance of the verse in the rules of ushul fiqh.